Comparative electrostatic analysis of adenylyl cyclase for isoform dependent regulation properties. Issue 12 (24th October 2016) - Tong, Rudi; Wade, Rebecca C.; Bruce, Neil J.
ABSTRACT: The enzyme adenylyl cyclase (AC) plays a pivotal role in a variety of signal transduction pathways inside the cell, where it catalyzes the cyclization of adenosine triphosphate (ATP) into the second‐messenger cyclic adenosine monophosphate (cAMP). Among other roles, AC regulates processes involved in neural plasticity, innervation of smooth muscles of the heart and the endocrine system of the pancreas. The functional diversity of AC is manifested in its different isoforms, each having a specific regulation pattern. There is an increasing amount of data available concerning the regulatory properties of AC isoforms, however little is known about the interactions on a structural level. Here, we conducted a comparative electrostatic analysis of the catalytic domains of all nine transmembrane AC isoforms with the aim of detecting, verifying and predicting the binding sites of molecular regulators on AC. The results provide support for the positioning of the binding site of the inhibitory protein Gi α at a pseudo‐symmetric position to the stimulatory Gs α binding site. They also provide a structural interpretation of the Gβγ interaction with ACs 2, 4, and 7 and suggest a new binding site for RGS2. Comparison of the small molecule binding sites on AC shows that overall they have high electrostatic similarity, but regions of electrostatic differences are identified. These could provide a basis for the development of novel compounds with isoform‐specific modulatory effects on AC. Proteins 2016; 84:1844–1858. © 2016 Wiley Periodicals, Inc.